2014
DOI: 10.1210/jc.2014-1517
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies a Novel Homozygous Mutation in the Phosphate Transporter SLC34A1 in Hypophosphatemia and Nephrocalcinosis

Abstract: The homozygous G>A transition that results in the substitution of histidine for arginine at position 495 of the renal sodium-dependent phosphate transporter, SLC34A1, is involved in disease pathogenesis in these patients. Our report of the second family with two mutated SLC34A1 alleles expands the known phenotype of this rare condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 20 publications
0
39
0
1
Order By: Relevance
“…Rajagopal et al reported another mutation in SLC34A1, p.Arg495His, in two siblings who presented with hypercalciuria and nephrocalcinosis [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajagopal et al reported another mutation in SLC34A1, p.Arg495His, in two siblings who presented with hypercalciuria and nephrocalcinosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…It has remained unclear whether human heterozygous mutations may be the cause of kidney stones [7,8]. The clinical findings in the first reported homozygous NaPiIIa mutation in human included Fanconi syndrome and bone disease without hypercalciuria or nephroalcinosis [9], while another paper described hypercalcemia and nephrocalcinosis without skeletal dysfunction [10]. Recent publications strengthen the involvement of SLC34A1 in hypercalcemia and kidney stones.…”
Section: Introductionmentioning
confidence: 99%
“…Magen et al 41 reported a clinical case of autosomal recessive hypophosphatemic rickets with renal Fanconi's Syndrome secondary to an Npt2a loss-of-function genetic mutation. Likewise, Rajagopal et al 42 and Kenny et al 43 both reported case studies of mutations in the Npt2a gene that resulted in phenotypes of renal phosphate wasting with resultant hypercalcemia, hypercalciuria, and hypophosphatemia. While these clinical reports suggest that the contribution of specific renal phosphate transporters to overall phosphate homeostasis may be more nuanced than previously recognized, they provide evidence and support for Npt2a as an important determinant of serum phosphorus, as well as a critical target of regulators of renal phosphate reabsorption.…”
Section: -mentioning
confidence: 99%
“…ClC5, FcRn, NaPi-IIa gene are related with metabolic renal disease. DAB2, GIPC has an uncertain meaning in human pathology, but their pathogenic effect must be explored [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].Considering the interaction between these genes, it would be very useful to analyze the relationship between polymorphisms of single base changes (SNP) of these genes, or the blocks of haplotypes and haplogroups that can be constructed with sets of SNP in T2D patients. Specially, the relationship of such variants with the development of peripheral neuropathy and the appropriate metformin doses.…”
mentioning
confidence: 99%
“…ClC5, FcRn, NaPi-IIa gene are related with metabolic renal disease. DAB2, GIPC has an uncertain meaning in human pathology, but their pathogenic effect must be explored [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%